Diet of Crossodactylus timbuhy (Anura: Hylodidae) in the Reserva Biológica Augusto Ruschi, state of Espírito Santo, Brazil - Campinhos, Elaine Costa; Ferreira, Rodrigo Barbosa; Mageski, Marcio Marques; Srbek-Araujo, Ana Carolina (Biota Neotropica, 2020)
Abstract: Anurans are predator and prey, playing an important role in ecosystem functioning. The diet composition is closely related to feeding strategy, and the information about prey items is useful to understand intra and interspecific interactions in trophic webs. Here we determined diet composition, feeding strategy, and relation between prey ingestion and body measures of Crossodactylus timbuhy, a recently described anuran species. We found 466 prey items from 20 prey categories in the stomach of 66 specimens (15 males and 51 females) of C. timbuhy. The diet consists mostly of Formicidae and Coleoptera, the items with the highest number, frequency of occurrence and prey importance. The diet composition was relatively similar to other species of Crossodactylus. Prey volume was positively related to frog size and weight, suggesting frogs may feed upon any prey they can swallow. Diet showed some variation between sexes. Despite females were larger and heavier than males, females had higher consumption of smaller prey, and ingested a larger number of prey categories. We suggest C. timbuhy has an invertebrate-opportunistic feeding habit. It is likely C. timbuhy uses a combination of ‘sit-and-wait’ and ‘active search’ strategies due to high consumption of both highly mobile and sedentary prey.